Case Report: Late-Onset Temporal Lobe Epilepsy Following Subarachnoid Hemorrhage: An Interplay Between Pre-existing Cortical Development Abnormality and Tissue Damage - Ikawa, Anna; Fujimoto, Ayataka; Arai, Yoshifumi; Otsuki, Yoshiro; Nozaki, Toshiki; Baba, Shimpei; Sato, Keishiro; Enoki, Hideo (Frontiers in Neurology, 2021)
Epileptogenicity following brain insult depends on various factors including severity of the resulting lesion and extent of brain damage. We report a 54-year-old female patient who developed medically refractory epilepsy resulting from the interplay of pre-existing and post-insult pathologies. She presented with subarachnoid hemorrhage (SAH) due to a ruptured aneurysm and underwent clipping surgery. Seizures started 3 months post-operatively. MRI revealed cerebral ischemia and hemosiderin deposits in the left temporal lobes, and left hippocampal atrophy was suspected. As anti-seizure medications and vagus nerve stimulation failed to control her seizures, she underwent left temporal lobe resection and placement of a ventriculoperitoneal shunt for the post-operative complication of hydrocephalus. She remains seizure-free to date. Neuropathology revealed a previously undiagnosed focal cortical dysplasia (FCD) type 1a. Brain insult likely had a second hit effect in the late onset of epilepsy in this patient with pre-existing mild MCD, in whom secondary epilepsy can be attributed to the interplay of multiple underlying pathologies.